INNOVATIVE TECHNOLOGIES IN LEARNING FOREIGN LANGUAGES (Conferencea, 2023)
The article reveals the place of modern educational technologies, including innovative and information and communication technologies in the process of teaching foreign languages, and their importance in improving the effectiveness of the educational process.